2023
DOI: 10.3390/genes14101852
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Complete Genome Sequence of an Avian Coronavirus Identified in a Backyard Chicken from Tanzania

Henry M. Kariithi,
Jeremy D. Volkening,
Gaspar H. Chiwanga
et al.

Abstract: A complete genome sequence of an avian coronavirus (AvCoV; 27,663 bp excluding 3′ poly(A) tail) was determined using nontargeted next-generation sequencing (NGS) of an oropharyngeal swab from a backyard chicken in a live bird market in Arusha, Tanzania. The open reading frames (ORFs) of the Tanzanian strain TZ/CA127/19 are organized as typical of gammaCoVs (Coronaviridae family): 5′UTR-[ORFs 1a/1b encoding replicase complex (Rep1ab) non-structural peptides nsp2-16]-[spike (S) protein]-[ORFs 3a/3b]-[small envel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Two complete genome sequences of IBVs (27,686 and 27,663 nt in length) were assembled from OP samples of chickens swabbed at central and Buguruni LBMs in Arusha and Dar es Salaam regions, respectively ( Table 4 ). Further analyses showed that one of the IBVs (strain 2,145-CA127; GenBank accession number OQ725698) is a recombinant virus with a backbone derived from an LX4-like IBV (lineage GI-19) virus and a turkey CoV-like S-gene; We have recently published the sequence data of this recombinant strain in a separate paper ( 66 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two complete genome sequences of IBVs (27,686 and 27,663 nt in length) were assembled from OP samples of chickens swabbed at central and Buguruni LBMs in Arusha and Dar es Salaam regions, respectively ( Table 4 ). Further analyses showed that one of the IBVs (strain 2,145-CA127; GenBank accession number OQ725698) is a recombinant virus with a backbone derived from an LX4-like IBV (lineage GI-19) virus and a turkey CoV-like S-gene; We have recently published the sequence data of this recombinant strain in a separate paper ( 66 ).…”
Section: Resultsmentioning
confidence: 99%